2017
DOI: 10.1002/ejp.1030
|View full text |Cite
|
Sign up to set email alerts
|

Pain thresholds, supra‐threshold pain and lidocaine sensitivity in patients with erythromelalgia, including the I848Tmutation in NaV 1.7

Abstract: Acute pain thresholds and supra-threshold heat pain in controls and patients with erythromelalgia do not differ and have the same lidocaine sensitivity. Acute heat pain thresholds even in EM patients with the Na 1.7 I848T mutation are normal and only nociceptor sensitivity to intradermal lidocaine is changed. Only in EM patients with mutations in Na 1.7, 1.8 or 1.9 supra-threshold heat and mechanical pain shows differential lidocaine sensitivity as compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(97 reference statements)
1
3
0
Order By: Relevance
“…Consistent with the distribution of Na v 1.7 channels on nociceptive sensory fibres, small fibre but not large fibre dysfunction has been demonstrated in children with IEM. 1,44,50 As also reported with other causes of neuropathic pain, 83,84 QST evaluation of small fiber function in IEM demonstrated mixed patterns of sensory gain and loss in adults, 18,53,76,[85][86][87][88] and in the 2 pediatric IEM cases reported here. The marked insensitivity to punctate stimuli in our p.I234T case correlated with a high tolerance for clinically required venipunctures, 28 the reduced sensitivity to injury associated with this genotype, [28][29][30] and a complex pattern that includes marked depolarization and lack of excitability in some DRG neurons expressing Na v 1.7-I234T channels.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the distribution of Na v 1.7 channels on nociceptive sensory fibres, small fibre but not large fibre dysfunction has been demonstrated in children with IEM. 1,44,50 As also reported with other causes of neuropathic pain, 83,84 QST evaluation of small fiber function in IEM demonstrated mixed patterns of sensory gain and loss in adults, 18,53,76,[85][86][87][88] and in the 2 pediatric IEM cases reported here. The marked insensitivity to punctate stimuli in our p.I234T case correlated with a high tolerance for clinically required venipunctures, 28 the reduced sensitivity to injury associated with this genotype, [28][29][30] and a complex pattern that includes marked depolarization and lack of excitability in some DRG neurons expressing Na v 1.7-I234T channels.…”
Section: Discussionsupporting
confidence: 83%
“… 67 The addition of suprathreshold QST paradigms might improve our ability to differentiate mechanistically relevant subgroups. 32 Larger replication studies will be needed to determine whether these phenotypic aspects could be used in the future to stratify patients for potential genetic testing. This could be relevant to future treatment choices, given the major effort to develop selective small molecule blockers of Na V 1.7, some of which are currently in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Further research has also identified that different genetic EM mutations may be responsible for the varying responses of individuals with hereditary EM to lidocaine treatment. Therefore, identifying the specific SCN9A genotype may provide guidance on treatment 41,42. Due to limited availability of genetic testing, current approach to the use of lidocaine may involve a trial and error strategy 43…”
Section: Pharmacotherapymentioning
confidence: 99%